Pomenski preplet glagolov imeti in biti - njuna jezikovnosistemska stilistika - Vidovič-Muha, Ada (Slavistična revija, 1998)
Verbal primitives (primary verbs) imeti (to have) anb biti (to be) are related by the expression of spatial location, but only biti is spatially open, indefinite, while imeti ties the orientation point to the possessor.- The semantic analysis is based on close transformational relation between verbs imeti and biti; the point of departure is the verb imeti. The possible transformational connections between the two vebs are through possessive adjective (T1), adverbial location (T2), and all others, non-possessive and non-spatial transformations (T3). The rich linguo-systemic stylistic, derived from these transformational relationships, is based on analyzing the sentence with respect to sentence perspective, i.e., it involves theme-rheme issues.
Keywords: glagol; Slovene; slovenščina; stilistika; stylistics; verb